Desenvolvimento de cultivares de goiabeira inoculadas com Meloidogyne enterolobii - Pereira, Kerly Cristina [UNESP]; Soares, Pedro Luiz Martins [UNESP]; Dos Santos, Jaime Maia [UNESP]; De Paula Batista, Elder Simões [UNESP]; Maldonado, Walter [UNESP] (My University, 2016)
The guava tree (Psidium guajava L.) is highly susceptible to the root-knot nematode Meloidogyne enterolobii, which causes significant losses in orchards. Due to these nematodes, many guava growers change to different crops, most of which are less profitable and require a higher technological production system. The aim of this work was to evaluate the development of the guava tree cultivars 'Paluma', 'Pedro Sato', 'Século XXI', and 'Tailandesa' parasitized by M. enterolobii and to compare parasitized plants with non-parasitized plants. Evaluations were carried out at 6 mo after nematode inoculation, and included plant height, stem diameter, fresh leaf mass, fresh roots mass, nematode root population, and the whole plant visual aspect. The tested cultivars were all hosts and allowed nematode population growth. 'Tailandesa' supported less nematode population growth than the other cultivars, and also had taller plants and higher mass of fresh leaves and roots. The overall visual appearance was also better for this cultivar, indicating greater tolerance to M. enterolobii.
Development of guava cultivars parasitized by Meloidogyne enterolobii
Keywords: Guava; Myrtaceae; Psidium guajava; Root-knot nematode